Penerapan Gaya Belajar KOLB Untuk Meningkatkan Pemecahan Masalah Matematika Siswa Di Kelas X SMK Negeri 1 Siabu - Bynoto Hutabarat; Haritsah Hammamah Harahap; Andi Saputra Mandopa (Program Studi Matematika Universitas Graha Nusantara Padangsidimpuan, 2025)
This study aims to improve student’s mathematical problem solving skills through the implemantion of Kolb’s learning style in class X TBSM @ at SMK Negeri 1 Siabu, focusing on the topic of sequences and series. The research method used is Classroom Action Research (CAR), conducted in two cycles, each consisting of planning, action, observation, and reflection. The research subjects were 20 students from class X. Data were collected through problem-solving tests, student and teacher activity observations, and analyzed using descriptive quantitative methods. The results showed an improvement in students’ problem-solving abilities from 55% (categorized as low) in the first cycle to 85% (categorized as good) in the second cycle. Observations also indicated increased student and teacher engagement and improvement in instructional quality. The implementation of Kolb’s learning style proved effective in helping students grasp mathematical concepts and problem-solving strategies. This research recommends the use of Kolb’s learning model as an alternative teaching approach to enhance students' critical thinking and learning outcomes in mathematics.